The role of positional environmental cues in movement regulation of Yurchenko vaults in gymnastics - Heinen, T.; Brinker, A.; Mack, M.; Hennig, L. (Science of Gymnastics Journal, 2017)
Numerous gymnastics skills demand a precise interaction between the gymnast and the environment. It remains unclear, how different environmental cues act and interact in the regulation of complex skills, such as Yurchenko-type vaults, where the gymnast performs a round-off before contacting the springboard. The aim of this study was to assess the roles of both, the position of the round-off mat and the position of the springboard, in the regulation of a Yurchenko timer. Kinematic parameters of eight female expert gymnasts` Yurchenko timers were examined in a baseline condition and two experimental conditions with different manipulations of the positions of the round-off mat and the springboard. Results revealed that visually controlled regulation of the run-up occurred in average two steps prior to the hurdle. Hand positioning on the round-off mat preceded a constant round-off flight phase. Gymnasts placed their feet on average on the same spot on the springboard, regardless of whether the springboard position was manipulated. Finally, hand positioning on the vault block mainly varied as a function of the position of the springboard and the distance of the flight phase to support. This study provides evidence that the position of the springboard regulates Yurchenko-type vaults. Knowledge about relationships between informational sources in the environment and the resulting motor behaviour in gymnasts may help coaches to develop training programs aiming to enhance gymnasts` ability to utilize this information in skill performance under changing environmental conditions in training and competition.